2023
DOI: 10.1159/000528962
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Timing of Diagnosis and Clinical Services Received in Duchenne Muscular Dystrophy

Abstract: Introduction: Racial/ethnic differences in diagnostic and treatment services have been identified for a range of health conditions and outcomes. The current study aimed to analyze whether there are racial/ethnic differences in the timing of diagnostic testing and treatments for males with Duchenne Muscular Dystrophy (DMD). Methods: Diagnostic and clinical data for male individuals with DMD born during 1990-2010 were analyzed from eight sites (Arizona, Colorado, Georgia, Iowa, Piedmont Region of North Carolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We were concerned that differences in FVC% decline in Hispanic and non-Hispanic boys might have re ected a different level of care. One previous study found that time to initiation of corticosteroid therapy of DMD was later among Hispanic individuals and rst pulmonary testing occurred earlier compared to non-Hispanic whites 30 . However, another study found that the average annual death rate of males with DMD age <40 years were higher in non-Hispanic whites than Hispanic whites 31 .…”
Section: Discussionmentioning
confidence: 91%
“…We were concerned that differences in FVC% decline in Hispanic and non-Hispanic boys might have re ected a different level of care. One previous study found that time to initiation of corticosteroid therapy of DMD was later among Hispanic individuals and rst pulmonary testing occurred earlier compared to non-Hispanic whites 30 . However, another study found that the average annual death rate of males with DMD age <40 years were higher in non-Hispanic whites than Hispanic whites 31 .…”
Section: Discussionmentioning
confidence: 91%
“…For example, the MD STARnet study on racial and ethnic differences in timing of diagnosis and clinical services received in Duchenne MD raises awareness of racial and ethnic disparities and could lead to educational efforts and earlier diagnoses in these populations. 19 When conducting surveillance and research on MD, it is important to include VHS as a data source. Mild cases of MD and those of later onset appear to be compatible in some cases with successful completion of military service.…”
Section: Discussionmentioning
confidence: 99%
“…This can potentially lead to measures that will ultimately improve the quality of life of individuals living with MD. For example, the MD STARnet study on racial and ethnic differences in timing of diagnosis and clinical services received in Duchenne MD raises awareness of racial and ethnic disparities and could lead to educational efforts and earlier diagnoses in these populations 19 . When conducting surveillance and research on MD, it is important to include VHS as a data source.…”
Section: Discussionmentioning
confidence: 99%
“… 6 For boys with DMD, diagnostic delays have remained unchanged over the past three decades, 7 with late diagnosis persistently noted in ethnic minority groups. 8 For many children, this results in missed opportunities for implementation of standards of care, participation in clinical trials, and access to newly approved dystrophin restoration therapies. Likewise, families lose opportunities for timely genetic counselling and testing.…”
Section: Introductionmentioning
confidence: 99%